2022
DOI: 10.1111/1751-7915.14133
|View full text |Cite
|
Sign up to set email alerts
|

Engineering cell morphology by CRISPR interference in Acinetobacter baylyiADP1

Abstract: Microbial production of intracellular compounds can be engineered by redirecting the carbon flux towards products and increasing the cell size. Potential engineering strategies include exploiting clustered regularly interspaced short palindromic repeats interference (CRISPRi)‐based tools for controlling gene expression. Here, we applied CRISPRi for engineering Acinetobacter baylyi ADP1, a model bacterium for synthesizing intracellular storage lipids, namely wax esters. We first established an inducible CRISPRi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…After water, the most abundant ingredients in cosmetic formulations are emollients, among which wax esters are the predominant ones. According to the available literature, these esters can be obtained through different green methods: the most widely used is extraction from natural sources, [1][2][3][4][5][6] followed by the not common microbiological production, [7][8][9] and the emerging enzymatic synthesis using lipases and natural substrates. [10][11][12] Spermaceti is a wax composed of various high molecular weight esters that is often used as a lubricant and in the pharmaceutical and food industries.…”
Section: Introductionmentioning
confidence: 99%
“…After water, the most abundant ingredients in cosmetic formulations are emollients, among which wax esters are the predominant ones. According to the available literature, these esters can be obtained through different green methods: the most widely used is extraction from natural sources, [1][2][3][4][5][6] followed by the not common microbiological production, [7][8][9] and the emerging enzymatic synthesis using lipases and natural substrates. [10][11][12] Spermaceti is a wax composed of various high molecular weight esters that is often used as a lubricant and in the pharmaceutical and food industries.…”
Section: Introductionmentioning
confidence: 99%
“…We first removed the complete lactate operon ( lldPRD , dld ; ACIAD 0106-0109) encoding a lactate permease, a l -lactate dehydrogenase operon regulator, a l -lactate dehydrogenase, and a d -lactate dehydrogenase. Furthermore, to increase the production of WEs, we overexpressed a fatty acyl-CoA reductase acr1 (ACIAD 3383), which has been previously shown to improve WE production in ADP1 [ 45 ]. We also showed that lactate concentrations relevant to what could be expected from the fermentation of the SLH containing approximately 38 g/L of sugars, e.g., up to 18 g/L lactic acid did not inhibit the growth of ASA714 (Additional file 1 : Fig.…”
Section: Discussionmentioning
confidence: 99%
“…First, a knockout cassette of acr1 was amplified from ADP1 Δ acr1 :: tdk/kan R as described previously [ 44 ] and used for transformation of ASA707 to obtain ASA710. For the overexpression of acr1, an integration cassette P t5 -acr1-kan R was amplified from the genome of a previously described strain ASA523 [ 45 ] and used to transform ASA710 to obtain ASA711. Next, the gene encoding the mScarlet fluorescence protein was integrated to ASA711 at the poxB (ACIAD 3381) site using a gene cassette described previously [ 36 ] to obtain the strain ASA714 used in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Primers were synthesized by Thermo Scientific and routine PCR amplifications were carried out using Phusion High Fidelity DNA Polymerase (New England Biolabs, UK). Chromosomal modifications were engineered in A. baylyi ADP1 by natural transformation of recipient strains with linear DNA fragments as described previously (Luo et al, 2020(Luo et al, , 2022a. First, regions of approximately 500 bp-1000 bp upstream (R1) and downstream (R2) of the target genes were amplified from the genomic DNA of A. baylyi ADP1.…”
Section: Genetic Modificationsmentioning
confidence: 99%